Irb Becomes E&HR - Kaebnick, Gregory E. (The Hastings Center report, 2019)
In January 2019, under the new name Ethics & Human Research, The Hastings Center relaunched its forty-year-old journal that focuses on the ethical, regulatory, and policy issues related to research with humans. Formerly called IRB: Ethics & Human Research, E&HR has the same editorial team, led by the Hastings scholar Karen Maschke, and is meant to continue the work of IRB but will also feature a greater range of scholarship on issues in science and health care that have implications for research with humans. While E&HR is formally a continuation of IRB, it feels like a new journal. It is similar in design and format to its sister journal, the Hastings Center Report, and it has a closely linked channel for publication and distribution. Like HCR, it is published through John Wiley & Sons in both paper and electronic formats. Its home on the Wiley Online Library is https://onlinelibrary.wiley.com/journal/25782363.